Identification of hub genes and signaling pathways related to gastric cells infected by Helicobacter pylori. (July 2021) - Gu, Shi-Yuan; Cao, Xun-Jie; Feng, Yi; Wei, Qing-Qian; Liang, Jia-Qi; Xie, Li-Min; Liu, Ye-Ling; Feng, Hui-Yin; Guo, Xu-Guang
Abstract: Background: Helicobacter pylori is a pathogen involved in several gastroduodenal diseases, whose infection mechanisms have not been completely confirmed. To study the specific mechanism of gastropathy caused by H. pylori, we analyzed the gene microarray of gastric mucosa and gastric cells infected by H. pylori through bioinformatics analysis. Methods: We downloaded GSE60427 and GSE74492 from the Gene Expression Omnibus (GEO) database, screened differentially expressed genes (DEGs), and identified the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) through R software. The Search Tool for the Retrieval of Interacting Genes (STRING) was applied to establish a protein–protein interaction (PPI) network and Cytoscape was used to identify the top seven hub genes. Besides, we also constructed the gene–microRNA(gene–miRNA) interaction through the miRTarBase v8.0 database by using the NetworkAnalyst tool. Results: One hundred and fifteen DEGs were screened out, with 54 genes up-regulated and 61 genes down-regulated, among which seven hub genes, including "IGF1R, " "APOE, " "IRS1, " "ATF3, " "LCN2, " "IL2RG, " and "PI3, " were considered as the main regulatory proteins in gastric cells when infected by H. pylori . Conclusion: In this study, hub genes and related signal enrichment pathways of gastropathy infected by H. pylori were analyzed through bioinformatics analysis based on the GSE60427 and GSE74492 datasets. Highlights: Bioinformatics revealed the signaling pathways related to Helicobacter pylori infection in gastric cells. Bioinformatics revealed the main differential genes of Helicobacter pylori infection in gastric cells. The study first found that IGF1R was down regulated in Helicobacter pylori with proper conjecture.